Muscle Infiltration in Chronic Lymphocytic Leukemia: A Diagnostic Challenge - Jiro Ichikawa; Keita Kirito; Tomonori Kawasaki; Kojiro Onohara; Masanori Wako; Hirotaka Haro (Diagnostics)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults but is rare in Asia. Extramedullary and extranodal manifestations in CLL are generally uncommon, and muscle involvement is extremely rare. A 70-year-old male with CLL presented with bilateral plantar pain, predominantly on the left side. Anemia and reduced platelet count prompted ibrutinib treatment. MRI revealed high-signal areas in the muscles, suggesting inflammation. Anemia and thrombocytopenia improved, but the pain persisted for 8 months. Histopathological findings confirmed CLL infiltration of the muscles. Radiotherapy alleviated the pain, and the patient remains under observation. Careful caution was needed because (1) MRI findings suggested an inflammatory lesion, broadening differential diagnosis, and (2) CLL may coexist with inflammatory diseases. Histopathological examination is essential for correct diagnosis and treatment.